1996
DOI: 10.1002/(sici)1097-4652(199608)168:2<373::aid-jcp16>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Turnover of the cystic fibrosis transmembrane conductance regulator (CFTR): Slow degradation of wild-type and ΔF508 CFTR in surface membrane preparations of immortalized airway epithelial cells

Abstract: The protein product of the cystic fibrosis (CF) gene, termed the cystic fibrosis transmembrane conductance regulator (CFTR), is known to function as an apical chloride channel at the surface of airway epithelial cells. It has been proposed that CFTR has additional intracellular functions and that there is altered processing of mutant forms. In examining these functions we found a stable form of CFTR with slow turnover in surface membrane preparations from CF and non-CF immortalized airway epithelial cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…A 50-fold increase in dark blue-staining cells, which represent a high expression of CFTR mRNA, was detected after transfection (Color Plate 2A) when compared with the cells that were treated with plasmid without lactosylated polylysine (Color Plate 2C). The number of moderately blue strained cells observed may represent endogenous CFTR, known to be present in these cells (Wei et al, 1996). The exon 14 sense probe showed only light blue stained cells (Color Plate 2B).…”
Section: Color Platementioning
confidence: 93%
See 1 more Smart Citation
“…A 50-fold increase in dark blue-staining cells, which represent a high expression of CFTR mRNA, was detected after transfection (Color Plate 2A) when compared with the cells that were treated with plasmid without lactosylated polylysine (Color Plate 2C). The number of moderately blue strained cells observed may represent endogenous CFTR, known to be present in these cells (Wei et al, 1996). The exon 14 sense probe showed only light blue stained cells (Color Plate 2B).…”
Section: Color Platementioning
confidence: 93%
“…In situ detection of the CFTR protein was with antibody pAb3145 followed by development with horseradish peroxidase (HRP)-labeled anti-rabbit antibody, and diaminobenzidine (DAB) reagent as described (Mulberg et al, 1995;Wei et al, 1996). Transfection with plasmid alone served as a control.…”
Section: Detection Of Cftr Proteinmentioning
confidence: 99%
“…Both CHO cell-and insect cell-expressed CFTR exhibited functional CFTR channel activity, but the activity of the insect-expressed CFTR was lower (1,33,48). The state of glycosylation of CFTR appeared to affect its stability at the plasma membrane (42,66).…”
Section: Vol 75 2007 Phagocytosis By Cho Cell-produced Sp-a Variantmentioning
confidence: 99%
“…However, the expression of ∆F508 CFTR in vivo might be different. Immunohistochemical studies performed on airway, intestinal, and hepatobiliary tissues (17,18,41,42) have demonstrated ∆F508 CFTR localization in the plasma membrane. Moreover, functional assays of transfected cells (43), in mice (44,45), and of human tissue specimens (18) have shown that ∆F508 CFTR is capable of transporting Clin response to cAMP agonists.…”
Section: Tablementioning
confidence: 99%